ANALISIS POTENSI WISATA MANGROVE EDUCATION PARK DI LABUHAN KECAMATAN SEPULU, KABUPATEN BANGKALAN MENJADI DESTINASI WISATA HALAL: Kurrotul Uyun Dwi - Kurrotun Uyun Dwi (JURNAL ADMINISTRASI NUSANTARA, 2022)
The tourism sector is a sector capable of increasing employment and economic growth. Currently halal tourism (halal tourism) is starting to be in great demand. Recorded as the country with the largest Muslim population in the world, Indonesia always makes improvements in the development of halal tourism, one example is on the island of Madura, especially in Bangkalan, namely the Mangrove Education Park Tourism which is in Labuhan Village, Sepulu District, Bangkalan Regency. This research was conducted to determine the tourism potential of the Mangrove Education Park in becoming a halal tourist destination. By using a research method that is descriptive qualitative and using a field study approach, it is hoped that this research can increase readers' understanding of halal tourist destinations and tourism potential that can have the opportunity to become halal tourist destinations.